Towards sustainable potato production in China: Optimizing nitrogen and water management with 5R strategies - Zhaolong Pan; Rong Jiang; Daijia Fan; Daping Song; Hanyou Xie; Xiya Wang; Wei Zhou; Ping He; Wentian He (European Journal of Agronomy, 2026)

Advancing autotrophic nitrogen removal in low C/N ratio wastewater: Innovative application of supercapacitor to enhance microbial electrolysis cells - Sen Fan; Yuhan Song; Decong Zheng; Xinyuan Peng; Sitao Li; Ping Gao; Daping Li (Journal of Environmental Sciences, 2025)

Integrating straw return and tillage practices to enhance soil organic carbon sequestration in wheat–maize rotation systems in the North China Plain - Hua Han; Daijia Fan; Shuxia Liu; Rong Jiang; Daping Song; Guoyuan Zou; Ping He; Minyu Wang; Wentian He (Agriculture, Ecosystems & Environment, 2025)

Trade-offs between agronomic and environmental benefits: A comparison of inhibitors with controlled release fertilizers in global maize systems - Minyu Wang; Ping He; Daijia Fan; Rong Jiang; Guoyuan Zou; Daping Song; Libo Zhang; Yu Zhang; Wentian He (Field Crops Research, 2025)

Global impact of enhanced-efficiency fertilizers on vegetable productivity and reactive nitrogen losses - Zhaolong Pan; Ping He; Daijia Fan; Rong Jiang; Daping Song; Lei Song; Wei Zhou; Wentian He (Science of The Total Environment, 2024)

Effects of nitrogen supply on hydrogen-oxidizing bacterial enrichment to produce microbial protein: Comparing nitrogen fixation and ammonium assimilation - Haoran Wang; Lixia Zhang; Chang Tian; Sen Fan; Decong Zheng; Yuhan Song; Ping Gao; Daping Li (Bioresource Technology, 2024)

Modelling adaptation measures to improve maize production and reduce soil N2O emissions under climate change in Northeast China - Daijia Fan; Daping Song; Rong Jiang; Ping He; Yaoyao Shi; Zhaolong Pan; Guoyuan Zou; Wentian He (Atmospheric Environment, 2024)

Efficient removal of heavy metals from aqueous solutions by Mg/Fe bimetallic oxide-modified biochar: Experiments and DFT investigations - Song Cheng; Weibo Meng; Baolin Xing; Changliang Shi; Qiang Wang; Daping Xia; Yanhe Nie; Gunyun Yi; Chuanxiang Zhang; Hongying Xia (Journal of Cleaner Production, 2023)

Improving potato productivity and mitigating nitrogen losses using enhanced-efficiency fertilizers: A global meta-analysis - Zhaolong Pan; Daijia Fan; Rong Jiang; Naeem Abbasi; Daping Song; Guoyuan Zou; Dan Wei; Ping He; Wentian He (Agriculture, Ecosystems & Environment, 2023)

Feasibility analysis of clean utilization of kitchen waste oil and lignite by co-fermentation treatment - Hongyu Guo; Bo Song; Daping Xia; Ze Deng; Linyong Chen; Yongjun Wang; Weizhong Zhao (Journal of Cleaner Production, 2023)

Effect of fat, oil and grease (FOG) on the conversion of lignite to biogenic methane - Bo Song; Daping Xia; Hongyu Guo; Zhiwei Dong; Yongjun Wang; Weizhong Zhao; Zhenhong Chen (Fuel, 2023)

Global evaluation of inhibitor impacts on ammonia and nitrous oxide emissions from agricultural soils: A meta‐analysis - Daijia Fan; Wentian He; Ward N. Smith; Craig F. Drury; Rong Jiang; Brian B. Grant; Yaoyao Shi; Daping Song; Yanhua Chen; Xuexia Wang; Ping He; Guoyuan Zou (Global Change Biology, 2022)
Inhibitors are widely considered an efficient tool for reducing nitrogen (N) loss and improving N use efficiency, but their effectiveness is highly variable across agroecosystems. In this study, we synthesized 182 studies (222 sites) worldwide to evaluate the impacts of inhibitors (urease inhibitors [UI], nitrification inhibitors [NI] and combined inhibitors) on crop yields and gaseous N loss (ammonia [NH 3 ] and nitrous oxide [N 2 O] emissions) and explored their responses to different management and environmental factors including inhibitor application timing, fertilization regime, cropping system, water management, soil properties and climatic conditions using subgroup meta‐analysis, meta‐regression and multivariate analyses. The UI were most effective in enhancing crop yields (by 5%) and reducing NH 3 volatilization (by 51%), whereas NI were most effective at reducing N 2 O emissions (by 49%). The application of UI mitigates NH 3 loss and increases crop yields especially in high NH 3 ‐N loss scenarios, whereas NI application would minimize the net N 2 O emissions and the resultant environmental impacts especially in low NH 3 ‐N loss scenarios. Alternatively, the combined application of UI and NI enables producers to balance crop production and environmental conservation goals without pollution tradeoffs. The inhibitor efficacy for decreasing gaseous N loss was dependent upon soil and climatic conditions and management practices. Notably, both meta‐regression and multivariate analyses suggest that inhibitors provide a greater opportunity for reducing fertilizer N inputs in high‐N‐surplus systems and presumably favor crop yield enhancement under soil N deficiency situations. The pursuit of an improved understanding of the interactions between plant‐soil‐climate‐management systems and different types of inhibitors should continue to optimize the effectiveness of inhibitors for reducing environmental losses while increasing productivity.

Pharmacokinetic Properties of Humanized IgG1 and IgG4 Antibodies in Preclinical Species: Translational Evaluation - Mohammad Tabrizi; Divas Neupane; Sophia E. Elie; Harish Shankaran; Veronica Juan; Shuli Zhang; SuChun Hseih; Laurence Fayadat-Dilman; Daping Zhang; Yaoli Song; Vaishnavi Ganti; Michael Judo; et al. (The AAPS Journal, 2019)